2020
DOI: 10.1021/acsinfecdis.0c00050
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin: A Critical Mediator of Both Host Immune Response and Antimicrobial Activity in Response to Streptococcal Infections

Abstract: Streptococcal species are gram positive bacteria responsible for a variety of disease outcomes including pneumonia, meningitis, endocarditis, erysipelas, necrotizing fasciitis, periodontitis, skin and soft tissue infections, chorioamnionitis, premature rupture of membranes, preterm birth, and neonatal sepsis. In response to streptococcal infections, the host innate immune system deploys a repertoire of antimicrobial and immune modulating molecules. One important molecule that is produced in response to strepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 114 publications
(233 reference statements)
2
18
0
Order By: Relevance
“…The antimicrobial activity of lactoferrin has been implicated in many bacterial species, as well as viruses, and fungi [32] . Our previous work demonstrated that recombinant lactoferrin could inhibit GBS growth via iron chelation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The antimicrobial activity of lactoferrin has been implicated in many bacterial species, as well as viruses, and fungi [32] . Our previous work demonstrated that recombinant lactoferrin could inhibit GBS growth via iron chelation.…”
Section: Discussionmentioning
confidence: 98%
“…In a systematic review of available literature, enteral lactoferrin supplementation decreases late‐onset sepsis and in combination with probiotics, may decrease necrotizing enterocolitis in preterm infants [31] . Lactoferrin also shows promise as an agent against streptococcal infections, [32] including a study demonstrating lactoferrin decreases biofilm formation in Streptococcus mutans [33] . Biofilms are multicellular structures that are critical for many bacterial pathogens, including GBS, to circumnavigate host defenses and persist in the hostile environment [34,35] .…”
Section: Introductionmentioning
confidence: 99%
“…LF kills pathogenic microorganisms by competitively seizing iron to lack sufficient iron replenishment to maintain biofilm structure and consequently die (51). LF binds to lipopolysaccharide (LPS) on the cell wall of gram-negative bacteria, killing the bacteria by altering cell membrane permeability (52,53). LF also has antiviral activity, preventing viruses from entering the host cell by blocking cellular receptors or directly binding to the virion (54).…”
Section: Lactoferrin (Lf)-lpn Complexmentioning
confidence: 99%
“…Lactoferrin is an iron-sequestering glycoprotein with antimicrobial properties that is highly expressed in milk during bovine mastitis (Harmon et al, 1976;Hagiwara et al, 2003;Chaneton et al, 2008). Due to its abundance and importance in host defense, many bacterial pathogens have evolved mechanisms for interacting with lactoferrin (Valenti and Antonini, 2005;Lu et al, 2020). S. uberis encodes two lactoferrin-binding proteins that demonstrate preference for bovine lactoferrin, in comparison to the human variant, and promote evasion of the antimicrobial properties of lactoferrin in the mammary gland niche (Fang and Oliver, 1999;Moshynskyy et al, 2003).…”
Section: Streptococcus Uberis Adhesion Moleculementioning
confidence: 99%